Life cycle cost and assessment model for systems and sources of lighting - Heteba, Noran (AUC Knowledge Fountain, 2013)
This research is concerned with the long-term enhancement of the systems and sources of lighting in Egypt. Lighting is at the top of the residential electricity consumption in Egypt with an estimated 34 percent. Internationally, lighting is only second to HVAC in residential electrical consumption. The methodology of this research is based on Life Cycle Costing (LCC) and Life Cycle Assessment (LCA). This methodology is crystallized through the formulation of an optimization model (LCCA-SSL) which integrates both LCC and LCA methods to help construction stakeholders in the decision making for the most sustainable lighting systems and lighting sources. This implementation can be part of an overall value engineering scheme. In an attempt to face the global problem of energy consumption, a case study has been selected to compare between two lighting systems; Conventional System and Photovoltaic Solar System, and their corresponding lighting sources; namely, light emitting diodes (LED), high pressure sodium (HPS), and metal halide (MH) within a 10 years period of analysis. The results showed that the lowest LCC selection is Photovoltaic Solar System using HPS Light Source. The best LCA selection is the Photovoltaic Solar System using LED light source which has the lowest carbon footprint. Consequently, the best integrated alternative between both LCC and LCA is Photovoltaic Solar System using HPS Light Source which has the lowest LCC and the second lowest carbon footprint. A sensitivity analysis was conducted in order to measure the impact of changing certain variables such as the interest rate, the inflation rate and the period of analysis, where there is uncertainty in their assumption, on the LCC of each of the alternatives. Despite of the similarities and the breakeven points between some of the alternatives’ LCC, Photovoltaic Solar System using HPS as a light source proved to have the least LCC among all the changing variables except for the inflation rate above 35%, where the Conventional System using LED started in beating the Photovoltaic Solar System using HPS to have the lowest LCC among all the other alternatives. The model proposed in this study is user friendly and can be used by different construction stakeholders to optimize the use of systems and sources of lighting under environmental and long-term constraints.